Implementasi Kebijakan Perlindungan dan Pengelolaan Lingkungan Hidup di Kota Dumai : (Studi Pengelolaan Kawasan Konservasi Laut Kecamatan Medang Kampai) - Dewi Nurhaliza; Febri Yuliani (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The Dumai City Government, through the Environmental Service, is trying to prevent abrasion by carrying out rehabilitation and reforestation by planting mangroves in coastal areas. The increase in sea levels that occurs throughout the world is also a factor in abrasion, resulting in erosion of the coastline in Dumai City. The Dumai City Environmental Service as a Regional Apparatus Organization (OPD) functions to assist the Regional Head in carrying out government duties, especially those related to environmental problems in areas that are expected to play an active role in overcoming environmental damage problems such as preventing coastal erosion. In carrying out its duties and authority, the Dumai City Environmental Service has a legal basis which serves as a guideline in preventing environmental damage problems such as abrasion in the coastal areas of Dumai City, this is contained in Dumai City Regional Regulation No. 5 of 2017 concerning environmental protection and management. This research is a qualitative research type with a case study approach, the required data such as primary data and secondary data are obtained through interviews and documentation and then analyzed based on the research problem. The results of this research show that conservation has evolved from exclusive protection to inclusive protection, involving communities and other stakeholders. Today's conservation is about how to control exploitative human behavior and practices. Efforts made by the Environmental Service are conducting outreach, mangrove planting activities with the community, community complaint facilities.